The STING in Non-Alcoholic Fatty Liver Diseases: Potential Therapeutic Targets in Inflammation-Carcinogenesis Pathway - Juan Lv; Chunlei Xing; Yuhong Chen; Huihui Bian; Nanning Lv; Zhibin Wang; Mingming Liu; Li Su (MDPI AG, 2022)
Non-alcoholic fatty liver disease (NAFLD), an important chronic disease, is one of the major causes of high mortality and creates a substantial financial burden worldwide. The various immune cells in the liver, including macrophages, NK cells, dendritic cells, and the neutrophils involved in the innate immune response, trigger inflammation after recognizing the damage signaled from infection or injured cells and tissues. The stimulator of interferon genes (STING) is a critical molecule that binds to the cyclic dinucleotides (CDNs) generated by the cyclic GMP-AMP synthase (cGAS) to initiate the innate immune response against infection. Previous studies have demonstrated that the cGAS-STING pathway plays a critical role in inflammatory, auto-immune, and anti-viral immune responses. Recently, studies have focused on the role of STING in liver diseases, the results implying that alterations in its activity may be involved in the pathogenesis of liver disorders. Here, we summarize the function of STING in the development of NAFLD and present the current inhibitors and agonists targeting STING.